Supersingular complete Edwards curves over a prime field - Bessalov, A.V.; Tsygankova, O.V. (Radiotekhnika, 2017)
The analysis of the conditions for the existence of super singular complete Edwards curves over a simple field is given. Three theorems are formulated and proved on the conditions for the existence of super singular curves with j-invariants equal to 0,123 and 663 .